[en] UNCOVERING THE WORK AND EDUCATION AREA: A STUDY ABOUT THE PRODUCTION AND THE PRODUCERS OF THE ANPED S WORK AND EDUCATION WORKGROUP - ALEXANDRE MAIA DO BOMFIM (MAXWELL, 2007)
[pt] Este estudo analisa a área de Trabalho e Educação, de modo a contribuir para a sua avaliação. Mais especificamente, a tese aborda a produção de pesquisa e os produtores do Grupo de Trabalho - Trabalho e Educação, o GTTE da Anped, durante o período 1996-2004, com o duplo objetivo de analisar a produção deste Grupo de Trabalho e de caracterizar quais são e como se dão as relações entre os o agentes responsáveis por essa produção. Para tal, foram analisados 132 trabalhos (incluindo alguns pôsteres), os resumos dos trabalhos encomendados, além das ementas dos mini-cursos disponibilizados nos CD-ROM e nos Cadernos das Reuniões Anuais da Anped. A análise inclui, também, documentos que realizam balanços da produção da área e a Plataforma Lattes do CNPq, consultada para obter informações sobre os seus autores Além disso, foram realizadas entrevistas com parte desses autores e com ex- coordenadores do GTTE. A tese é construída em torno da problematização da tradição analítico-metodológica que caracterizaria o GT e que influencia suas escolhas e preferências. O estudo permite constatar que a identidade do grupo ligada à perspectiva marxista constituiu uma pauta nos anos 80 que não conseguiu ainda ser cumprida. Constata, também, que a década de 90 trouxe novos desafios para o GTTE e que a manutenção da perspectiva teórica hegemônica do grupo o colocou diante da difícil escolha entre mais ortodoxia ou mais heterodoxia. A pesquisa mostra que os maiores desafios do GT estão no diálogo com a Escola Básica, na reflexão sobre as políticas públicas, nos estudos de setores não- industriais, nos estudos históricos, nas análises macro ou panorâmicas e na reflexão sobre experiências alternativas e contra-hegemônicas. === [en] This study analyses the area of Work and Education, in way to contribute to its evaluation. More specifically, the thesis approaches the research production and the producers of the Workgroup - Work and Education, the GTTE of Anped, during the period 1996-2004, with the double objective of analyzing the production of this Workgroup and of characterizing who they are and how the relationships occur between the producing agents of this production. For this, 132 papers (including some posters) were read and filed, and the summaries of the invited papers, besides the contents of the available mini- courses in the CD-ROM and the Paper Summaries of Anped Annual Meetings. Besides that, documents that present the balance of the production of the area were studied and it was used the Lattes Platform of CNPQ in order to gather information about the researchers which participate of this Workgroup. Interviews with ex-coordinators and researchers of the GTTE were also made. This thesis problemizes the analytic-methodological tradition that should characterize the Workgroup and influences its choices and preferences. The study of the production of the GTTE allows to note: that the identity of the group been connected of the Marxist perspective constituted a guideline in the 80´s that still has not been managed to be carried out. It notes also that the decade of 90´s brought new challenges to the GTTE and that the maintenance of the hegemonic theoretical perspective of the group brought it to face a difficult choice between more orthodoxy or more heterodoxy. The inquiry shows that the biggest challenges of the Workgroup are in the dialog with the Basic School, in the reflection on the public politics, in the studies of non-industrial sectors, in the historical studies, in the macro or panoramic analyses and in the reflection on alternative and counter hegemonic experiences.